Penerapan Metode Diskusi untuk Meningkatkan Minat Belajar Pendidikan Agama Islam di Kelas IV UPT SDN 03 Pancung Soal - Sari, Siska Permata (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effectiveness of the Talking Stick learning model in improving students’ critical thinking skills. The research was conducted using the Classroom Action Research (CAR) approach, implemented in two cycles. The results showed that the application of this learning model effectively increased student engagement and participation in learning. In the first cycle, although there was an improvement, some challenges remained in implementing this model. However, after improvements were made in the second cycle, the results showed a significant enhancement in students’ critical thinking abilities. Therefore, it can be concluded that the Talking Stick model is effective in improving students’ critical thinking skills.